The Salutation or Monstrosities for 1818. - Cruikshank, George, 1792-1878 ? (McCleary, 1818)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Fashion ? History -- 19th century; Dandies